2011
DOI: 10.1016/j.resuscitation.2011.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Association between Cerebral Performance Category, Modified Rankin Scale, and discharge disposition after cardiac arrest

Abstract: Background Cerebral Performance Category (CPC), Modified Rankin Scale (mRS) and discharge disposition are commonly used to determine outcomes following cardiac arrest. This study tested the association between these outcome measures. Methods Retrospective chart review of subjects who survived to hospital discharge between 1/1/2006 and 12/31/2009 was conducted. Charts were reviewed for outcomes (CPC, mRS, and discharge disposition). Discharge disposition was classified in 6 categories: home with no services, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
143
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 202 publications
(151 citation statements)
references
References 20 publications
7
143
1
Order By: Relevance
“…Our finding is consistent with a previous study in which caregiver's psychological morbidity was equal to or greater than the patient's (Xian et al, 2011). In another previous study, almost 40% of the spouse caregivers reported depressive symptoms in a range that was likely to be clinically significant, a prevalence that was almost two-fold than their ill partners (Rittenberger et al, 2011). Previous studies have demonstrated that caregivers of patients with cancer have increased health problems and psychosocial stress (Bergen-Jackson et al, 2009;Kiely et al, 2010;Zhou et al, 2010;Bell et al, 2011;Gilbertson-White et al, 2011;Legler et al, 2011;Stevens et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding is consistent with a previous study in which caregiver's psychological morbidity was equal to or greater than the patient's (Xian et al, 2011). In another previous study, almost 40% of the spouse caregivers reported depressive symptoms in a range that was likely to be clinically significant, a prevalence that was almost two-fold than their ill partners (Rittenberger et al, 2011). Previous studies have demonstrated that caregivers of patients with cancer have increased health problems and psychosocial stress (Bergen-Jackson et al, 2009;Kiely et al, 2010;Zhou et al, 2010;Bell et al, 2011;Gilbertson-White et al, 2011;Legler et al, 2011;Stevens et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…There were some studies about burden of caregivers of terminally ill patients (Bekelman et al, 2011;Nelson et al, 2011;Rittenberger et al, 2011;Xian et al, 2011). However, to our knowledge, there had been few studies to compare burden of terminal cancer patients and their caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason mRS ϭ 3 was still considered a good outcome when dichotomizing the scale. 10 Among factors for good clinical outcome, time from onset of symptoms to recanalization is considered one of the key factors, with an increasing time span to recanalization decreasing the chances of success for the rescue of tissue at risk. 22 In our investigation, various time factors were assessed but, as shown in previous investigations, did not show a statistically significant influence on clinical outcome.…”
Section: Prognostic Value Of Hyperattenuated Intracerebral Lesionsmentioning
confidence: 99%
“…The collected data were based on the Utstein template [15,16] and included the region, place, patient's age, patient's sex, arrest witness, causes of arrest (presumed cardiac or not), bystander CPR, initial cardiac rhythm, estimated time of collapse, times of the initiation of CPR by bystanders and EMTs, interval between the emergency call and arrival at the patient, sustained return of spontaneous circulation (SROSC), one-month (1-M) survival, one-year (1-Y) survival and 1-Y survival with a favourable neurological outcome, determined based on the Pittsburgh cerebral performance category (CPC) [17,18]. The times of collapse and the initiation of CPR by bystanders were estimated by an interview, as reported previously [4].…”
Section: Populations and Settingmentioning
confidence: 99%